2007
DOI: 10.1093/rheumatology/kel269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characterization of Italian patients affected by CINCA syndrome

Abstract: Despite some common signs-used as syndrome hallmarks-we observed a high variability in symptoms, genetic results and outcomes in Italian CINCA patients. In contrast with other authors, we cannot find out any correlation between mutations in CIAS1 and CINCA severity, but we underlined the concomitance of perinatal events and mental retardation only in CIAS1 mutated subjects. Finally, we confirmed the efficacy of Anakinra treatment, both in CIAS1-mutated and non-mutated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Among the patients examined in this study, C5 lacked NLRP3 mutations but displayed clinical manifestations clearly consistent with a CINCA syndrome (29) and the same redox alterations observed in mutated CINCA monocytes (Figs. 2 and 3).…”
Section: Discussionsupporting
confidence: 58%
“…Among the patients examined in this study, C5 lacked NLRP3 mutations but displayed clinical manifestations clearly consistent with a CINCA syndrome (29) and the same redox alterations observed in mutated CINCA monocytes (Figs. 2 and 3).…”
Section: Discussionsupporting
confidence: 58%
“…CIAS1 -associated periodic syndrome patients ( 10,11 ), as well as the involvement of NLRP1 and NLRP3 polymorphisms in the predisposition to several autoimmune disorders ( 5 -8 ), we evaluated the possible association between selected polymorphisms in NALP1 / NLRP1 and CIAS1 / NALP3 / NLRP3 genes and CD in Italian patients. NLRP1 single-nucleotide polymorphisms (SNPs) rs12150220 and rs2670660 were chosen, as they have been previously associated with immune disorders ( 4,5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical characteristics of the study patients are shown in Table 1. The CINCA syndrome patients have been described in part elsewhere (28). Disease onset occurred within the first month of life in most of the study patients.…”
Section: Methodsmentioning
confidence: 99%